Tsubasa: Reservoir Chronicle: entre el śūnyatā y la posmodernidad - Castelli Olvera, Sarahi Isuki (El Colegio de México, 2022)
This article argues that the Tsubasa: Reservoir Chronicle manga, by CLAMP collective and published in Japan from 2003 to 2009, has a narrative structure based on a dialogue where religious philosophy converges with postmodern ideas. This argument is in contrast to the proposals of traditionalist discourse, which emphasizes the distinctive features of the Japanese tradition, thus tending to overlook the historical impact of the foreign Other. The analysis is based on the paradigm of indicial inferences of microhistory, with the identification of significant details. Postmodernism provides the theoretical reference points in two ways: one Eastern and the other Western, as suggested by Steven Heine, Fredrick Jameson, and Jean Baudrillard.